Rancang Bangun Mobile Commerce “Dodolan” Produk UMKM Batik Trusmi - Ade Rizki Rinaldi; Gifthera Dwilestar; Aria Pratama; Muhamad Abdurrohman; Mulyawan Mulyawan (JURIKOM (Jurnal Riset Komputer), 2022)
Marketplace is expected to be a solution in streamlining activities between sellers and buyers. Information systems that discuss distribution and sales among batik craftsmen are very rare. Especially information systems regarding the distribution and sale of products from batik craftsmen, the development of information is very minimal in the current era of technology and information. The purpose of the dodolan application Marketplace is a location for buying and selling products where sellers and buyers meet in a place or referred to as an electronic market. By using this system, the craftsmen can inform the results to outsiders quickly through the marketplace concept which will be built using the Business to Business (B2B) concept. Based on the observations of batik artisans in the Trusmi area, the marketing and sales system still uses the conventional one where the craftsmen sell their products to the showroom of their handicrafts, so that the selling price obtained by batik craftsmen is relatively cheaper. In addition, the conventional buying and selling marketing system is considered less effective from the point of view of time because it has to send goods to a shoroom that is quite far away. The result of making the "Dodolan" Mobile Commerce application is to break the sales chain from craftsmen to batik showroom sellers. So that batik craftsmen do not need to sell their results to batik sellers' sorum, with the intention that craftsmen can get greater profits. This Android-based batik "Dodolan" Mobile Commerce application can carry out the buying and selling process that can be accessed by buyers and admins. Buyers can process purchases, while admins can process purchase transactions and can also sell products